Господарські заняття українців - Івашиненко, К. В. (ХНУРЕ, 2020)
The Ukrainian calendar and everyday customs and ceremonies were a difficult and long way of development. They got this name because of the connection with calendar cycles (winter, spring, summer, autumn), on which the life of our ancestors directly depended. Sometimes they are also called agrarian, ie associated with certain types of economic work (sowing, planting crops, harvesting).
Keywords: культурне розмаїття; українознавство; традиції; культура